2020
DOI: 10.1111/1365-2478.12996
|View full text |Cite
|
Sign up to set email alerts
|

New insights from legacy seismic data: reprocessing of legacy 2D seismic data for imaging of iron‐oxide mineralization near Sishen Mine, South Africa

Abstract: Two overlapping legacy seismic profiles, 130 km long end to end, were shot in the 1990s over the Kuruman Hills on the western margin of the Kaapvaal Craton in southern Africa. The 6‐s profiles were aimed at investigating the crustal structure of the western Kaapvaal Craton as well as to locate potential continuation of the Witwatersrand gold‐bearing horizons beneath the cover rocks, the latter of which was unsuccessful. In this study, the legacy seismic data are reprocessed and used to image the iron‐oxide (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…21 m. Theoretically, this implies that two or more geological features within 21 m of each other will not be resolved as separate features. However, smaller features could still be detected, but this will depend on signal‐to‐noise ratio of the data, the velocity field and the migration algorithm used for migration (Manzi et al ., 2014; Westgate et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…21 m. Theoretically, this implies that two or more geological features within 21 m of each other will not be resolved as separate features. However, smaller features could still be detected, but this will depend on signal‐to‐noise ratio of the data, the velocity field and the migration algorithm used for migration (Manzi et al ., 2014; Westgate et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The two unconformities (U1 and R1) are clearly mapped due to the high acoustic impedance contrast between the overlying Karoo strata with low velocities (∼4000 m/s) and densities (∼2.10 g/cm 3 ) and the underlying Ventersdorp basaltic lavas with high velocities (∼6400 m/s) and densities (∼2.90 g/cm 3 ) (Westgate et al, 2020). The contact between the Ventersdorp basaltic lavas and the underlying Central Rand Group quartzite with relatively lower velocities (∼5400 m/s) and densities (∼2.67 g/cm 3 ) also exhibit a significant acoustic impedance contrast (Manzi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a better understanding of the velocity fields from hard rock environment has shown significant improvement in depth imaging of complex geological structures. Several authors (e.g., Malehmir et al, 2019; Manzi et al, 2019; Westgate et al, 2020) have demonstrated, through various case studies from hard rock environments, how legacy reflection seismic data can be revisited and reprocessed to improve the quality of the data and delineate the complex geological structures that host mineral deposits. The objective of this study is to reprocess the 18 km long, 6 s two‐way time (TWT), legacy 2D reflection seismic profile acquired in 1993 near Burnstone mine in the South Rand goldfield of the Witwatersrand Basin (South Africa).…”
Section: Introductionmentioning
confidence: 99%
“…The journey from initial consideration, proof-of-concept, proof-of-value to adoption is long but constitutes almost half of the roadmap to a dominantly automated context (Global Mining Guidelines Group, 2019). The history of mining is extensive, and particularly in South Africa where underground mining has generated enormous amounts of irreplaceable data (e.g., Manzi et al, 2015;Westgate et al, 2020;Zhang et al, 2021b;Nwaila et al, 2022). However, legacy data can be difficult to comprehend, as metadata, reference data and other supplementary information are incomplete, missing or not machine readable.…”
Section: Value Of Legacy Data In Underground Miningmentioning
confidence: 99%